Performance Analysis of 3 Arms Without Signal Access (Case Study Jl. Raya Bogor-Sukabumi, Jl. Siliwangi-Cibolang, Jl. Perintis Kemerdekan) - Nurul Aen; Daniel Ari Susanto; Dio Damas Permadi; Isaeva Tatyana Evgenevna (Nusa Putra University, 2021)
One of the types of intersections is the type of unsignalized intersection, the unsignalized intersection which is on Jl. Raya Bogor-Sukabumi, Jl. Siliwangi- cibolang, Jl. Independence pioneer. is the intersection of three arms. This study aims to determine the value of cur/hour and the performance of unsignalized intersections at the intersection. This research method is a field survey, which is carried out by researching directly in the field to obtain the required data. calculation of unsignalized intersection performance data using the 1997 Indonesian Highway Capacity manual method. Results the analysis obtained, the value of capacity from seven days of observation obtained a value of….cur/hour, the value of the degree of saturation DJ=….., too high occurred on the day… at WIB and the value of the delay is obtained by…. sec/cur. The queue probability value ranges from….% -….%